Inflammatory Pericardial Pseudocyst Secondary to Atrial Myocardial Perforation: A Rare Complication following Transvenous Pacemaker Implantation - Mohammad Mowaswes; Tawfik Khoury; Ziv Lahav; Ashraf Sanduka; Ayelet Shapira-Daniels; Oz M. Shapira (Case Reports in Cardiology)
Pericardial cyst is an uncommon clinical-pathological entity, most often a congenital condition. We describe a case of an acquired iatrogenic pericardial pseudocyst following permanent pacemaker implantation secondary to atrial myocardial perforation. Diagnosis was achieved by a plain chest film, echocardiography, and computed tomography and confirmed intraoperatively. The pseudocyst was resected via a midline sternotomy approach. The patient recovered uneventfully. In a follow-up of 18 months, the patient is doing well.